Development of Pbl-Based E-Module of Transport and Substance Exchange Process to Improve Critical Thinking Skills of Senior High School Students - Solehuddin, Muhammad; Susilo, Herawati; Gofur, Abdul (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
21st century education must be adapted to the demands of the times so that students are able to compete in the future. One of the 21st century skills needed in learning is critical thinking. Learning that supports critical thinking skills is the problem-based learning model (PBL). The problem-based learning model can have a significant effect on critical thinking skills. Students are required to have critical thinking skills to be able to compete competitively. One of the innovations in biology learning is the development of e-module of Substance Transport and Exchange Process to train students' critical thinking skills. This e-module development uses the ADDIE development model. The e-module of the Substance Transport and Exchange Process after being validated obtained a very valid validity, namely the results of media validation obtained an average of 95.5% with a very valid category, the results of material validation were 100% with a very valid category. The results of practicality are very practical, namely individual trials (one to on trial) obtained an average of 82.22% with a very practical category, small group trials obtained an average of 86.26% with a very practical category, practicality of biology education practitioners obtained an average of 100% with a very practical category. Effectiveness test to improve students' critical thinking skills. The average result of each indicator of critical thinking skills pretest is 35.86 and posttest is 59.78 which indicates an increase in students' critical thinking skills with N-Gain results of 0.3 with moderate effectiveness category. Data on the percentage of PBL model implementation showed an average value of each stage carried out of 91.7% with a very implemented category.